Fixed and flexible exchange rates and currency sovereignty - Claudio Sardoni; L. Randall Wray (Levy Economics Institute of Bard College, 2007)
This paper provides an analysis of Keynes's original Bancor proposal as well as more recent proposals for fixed exchange rates. We argue that these schemes fail to pay due attention to the importance of capital movements in today's economy, and that they implicitly adopt an unsatisfactory notion of money as a mere medium of exchange. We develop an alternative approach to money based on the notion of currency sovereignty. As currency sovereignty implies the ability of a country to implement monetary and fiscal policies independently, we argue that it is necessarily contingent on a country's adoption of floating exchange rates. As illustrations of the problems created for domestic policy by the adoption of fixed exchange rates, we briefly look at the recent Argentinean and European experiences. We take these as telling examples of the high costs of giving up sovereignty (Argentina and the European countries of the EMU) and the benefits of regaining it (Argentina). A regime of more flexible exchange rates would have likely produced a more viable and dynamic European economic system, one in which each individual country could have adopted and implemented a mix of fiscal and monetary policies more suitable to its specific economic, social, and political context. Alternatively, the euro area will have to create a fiscal authority on par with that of the U.S. Treasury, which means surrendering national authority to a central governmentan unlikely possibility in today's political climate. We conclude by pointing out some of the advantages of floating exchange rates, but also stress that such a regime should not be regarded as a sort of panacea. It is a necessary condition if a country is to retain its sovereignty and the power to implement autonomous economic policies, but it is not a sufficient condition for guaranteeing that such policies actually be aimed at providing higher levels of employment and welfare.
Keywords: E12; E63; F31; F33; F36; 330; Foreign Exchange; International Monetary Arrangements; Economic Integration; Stabilization; Keynes; Fester Wechselkurs; Flexibler Wechselkurs; Keynesianismus; Postkeynesianismus; Währungspolitik; Souveränität; Theorie; Argentinien; EU-Staaten